2018
DOI: 10.1007/s11547-018-0866-7
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamic susceptibility contrast (DSC) perfusion MRI in differential diagnosis between radionecrosis and neoangiogenesis in cerebral metastases using rCBV, rCBF and K2

Abstract: DSC-MRI appears a clinically useful method to differentiate between tumor recurrence, tumor necrosis and pseudoprogression in patients treated for cerebral metastases. Relative CBV using a cut-off value of 2.1 proved to be the most accurate and reliable parameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 25 publications
0
46
0
Order By: Relevance
“…In the follow-up, recurrences often display similar imaging features to therapy-related changes, such as pseudoprogression or radionecrosis, and perfusion MRI is generally used to distinguish these conditions. For instance, dynamic susceptibility contrast perfusion has shown to be helpful for differentiating tumor recurrence, tumor necrosis, and pseudoprogression in patients treated for cerebral metastases, with relative cerebral blood volume of 2.1 having proven to be the most accurate perfusion parameter [ 6 ]. In this setting, the fifth percentile of the ADC histogram at a high b -value and mean ADC ≤ 1.3 × 10 −3 mm 2 /s allowed the differentiation between glioblastoma recurrence and treatment-related changes indicative of pseudoprogression [ 7 ].…”
Section: Neuromentioning
confidence: 99%
“…In the follow-up, recurrences often display similar imaging features to therapy-related changes, such as pseudoprogression or radionecrosis, and perfusion MRI is generally used to distinguish these conditions. For instance, dynamic susceptibility contrast perfusion has shown to be helpful for differentiating tumor recurrence, tumor necrosis, and pseudoprogression in patients treated for cerebral metastases, with relative cerebral blood volume of 2.1 having proven to be the most accurate perfusion parameter [ 6 ]. In this setting, the fifth percentile of the ADC histogram at a high b -value and mean ADC ≤ 1.3 × 10 −3 mm 2 /s allowed the differentiation between glioblastoma recurrence and treatment-related changes indicative of pseudoprogression [ 7 ].…”
Section: Neuromentioning
confidence: 99%
“…Unfortunately, published data have been inconsistent. Hu et al reported rCBV of < 0.71 as 92% sensitivity and 100% specificity for radiation necrosis, while another suggested a rCBV cutoff of < 2.1 (100% sensitivity and specificity) ( 38 , 41 ). Barajas et al reported significant overlap in rCBV values and proposed using the percentage of signal-intensity recovery (PSR) ( 33 ).…”
Section: Diagnosis and Investigations For Patients With Suspected Rnmentioning
confidence: 99%
“…27 MRI spectroscopy using ratios of choline/creatine and/or choline/N-acetyl aspartate may contribute to a better distinction of radionecrosis, but is limited in small lesions and in the posterior fossa. 18,28 A combination of 18 F-FET PET and perfusion-weighted MRI was shown to improve the accuracy of glioma grading compared with MRI alone. 29 Specific literature data on the use of this combined technique for radiation necrosis vs vital brain metastases are currently lacking.…”
Section: Discussionmentioning
confidence: 99%